Toussaint Louverture and the American Civil War : the promise and peril of a second Haitian revolution - Clavin, Matthew J. (University of Pennsylvania Press, 2010)
"The Haitian Revolution cast a long shadow over the Atlantic world. In the United States, according to Matthew J. Clavin, there emerged two competing narratives that vied for the revolution's legacy. One emphasized vengeful African slaves committing unspeakable acts of violence against white men, women, and children. The other was the story of an enslaved people who, under the leadership of Louverture, vanquished their violent oppressors in an effort to eradicate slavery and build a new nation. Toussaint Louverture and the American Civil War examines the significance of these competing narratives in American society on the eve of and during the Civil War"--Jacket